2022
DOI: 10.2355/isijinternational.isijint-2021-318
|View full text |Cite
|
Sign up to set email alerts
|

Wear and Corrosion Resistance of CrN Films on Oxynitriding-treated Vanadis 8 Tool Steel <i>via</i> the DC Magnetron Sputtering Process

Abstract: This research coated CrN films on oxynitriding-treated Vanadis 8 tool steel using the DC magnetron sputtering process of the PVD technique. The experimental parameters include different gas flow rates (Ar/N 2 was 20/20, 24/16, 28/12, and 32/8, respectively), with a bias of − 50 V, power of 100 W, deposition temperature of 300°C, and deposition time of 180 min, respectively. The experimental results show that Vanadis 8 tool steel can form an effective oxynitriding layer with a depth of about 50 μm after the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Furthermore, most literature points out that CrN lms have various preferential growths in the PVD process and that CrN lms have different growth directions under different coating parameters [9,14]. In this study, as the main diffraction peaks of different deposition temperatures were still the same degrees, this result is consistent with previous literature [4,9,14].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, most literature points out that CrN lms have various preferential growths in the PVD process and that CrN lms have different growth directions under different coating parameters [9,14]. In this study, as the main diffraction peaks of different deposition temperatures were still the same degrees, this result is consistent with previous literature [4,9,14].…”
Section: Resultssupporting
confidence: 92%
“…In this study, both the lowest corrosion current (8.9×10 − 5 A•cm − 2 ) and highest polarization resistance (822.11 Ω•cm 2 ) appeared in the 325℃ sample. Our previous studies indicated that the samples with a lower corrosion current (I corr ) and a higher polarization resistance (R P ) exhibited better corrosion resistance [4,6,7], thus, the 325℃-deposited CrN lms had the best corrosion resistance. It is speculated that the above phenomenon is mainly caused by the density difference on the surface of the CrN coating (as seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations